2011
DOI: 10.4040/jkan.2011.41.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal Colonization and Ventilator-associated Pneumonia in Mechanically Ventilated Patients according to Type of Endotracheal Suction System

Abstract: Purpose: This study was conducted to identify endotracheal colonization and the incidence of ventilator-associated pneumonia related to the type of endotracheal suction system. Methods: The participants in this study were ICU patients hospitalized between October 2009 to March 2010 who used ventilators for over 48 hr with closed (CSS, n= 30) or open (OSS, n= 32) suction systems. To standardize the pre-intervention suction system, a suctioning protocol was taught to the ICU nurses. Collected data were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…Closed suction systems may be more effective for the ICU environment where ICU bed density is too high. In fact, some Korean studies showed closed suction system outperforms open suctioning in reducing infections [9][10][11]. In this study, there were no differences between the experimental and control catheters with respect to the incidence of hypoxia, hemodynamics, infection and ICU length of stay probably because both were closed-suction catheters.…”
contrasting
confidence: 66%
See 2 more Smart Citations
“…Closed suction systems may be more effective for the ICU environment where ICU bed density is too high. In fact, some Korean studies showed closed suction system outperforms open suctioning in reducing infections [9][10][11]. In this study, there were no differences between the experimental and control catheters with respect to the incidence of hypoxia, hemodynamics, infection and ICU length of stay probably because both were closed-suction catheters.…”
contrasting
confidence: 66%
“…Closed suctioning, backed by continuous supply of oxygen and positive end-expiratory pressure, is said to provide physiological stability and reduce the risk of nosocomial infection by keeping ventilator circuit closed. [6][7][8][9][10][11][12] However, its efficacy in preventing infections is still debated. [13,14] Newly developed closed-suction catheter (AceTrachcare, AceMedical Co., Republic of Korea) has dial-type pressure valve, located on the suction port, enables physicians to vary the level of suction pressure depending on the amount of secretions ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CSS can reduce contamination in the respiratory system because it allows endotracheal suctioning without disconnection of the patient from the ventilator. 39 Selection of an appropriate size SC in a CSS can help conserve the minute volume and PEEP to improve the clinical signs of hypoxemia and limit environmental, personnel, and patient contamination during suctioning. Therefore, closed system suctioning may be particularly beneficial in critically ill patients with respiratory conditions, such as patients with COVID-19.…”
Section: Comparison With Past Study Findingsmentioning
confidence: 99%
“…Colonized resistant strains can spread to other patients or contaminate the hospital surroundings via transmission by the medical staff or medical devices [14]. Pneumonia, in particular, increases mortality and disease prevalence and is a critical threat to patient safety [16]. The health-care cost of HAIs is considerable [14], and the annual cost of managing these infections at a 100-bed hospital has been estimated at 78,511,500 KRW [17].…”
Section: Introductionmentioning
confidence: 99%